ZIKA Virus, an Emerging Arbovirus in India: A Glimpse of Global Genetic Lineages - Paramasivan Rajaiah; Bhavna Gupta; Muniyaraj Mayilsamy (Microorganisms)
ZIKA fever (ZIKAF) is an emerging mosquito-borne flavivirus illness in humans. Regarding the etiological agent, ZIKA virus (ZIKAV), though it is known to be distributed in the tropics, causing sporadic cases, its rapid global expansion with pandemic potential has raised global concern. Due to its abrupt emergence in South American countries, the Caribbean, and the Americas, the WHO declared ZIKA a public health emergency of international concern in 2016. ZIKAV usually causes mild infections; however, its recent unusual presentations of Guillen–Barré syndrome in adults and microcephaly in newborn babies of ZIKAV-infected mothers in Brazil has caused concern among global public health authorities. Certain mutations on virus genomes have been found to be correlated with clinical severity, and its unusual transmission routes through sexual and blood transfusions emphasize the necessity for understanding its virological determinants and impact. Its abrupt re-emergence in India (2018–2019), particularly in Gujarat (2016), Tamil Nadu (2017), Uttar Pradesh (2021), Maharashtra, Kerala (2021), and Karnataka (2023), has indicated the need for urgent measures to strengthen surveillance systems and design effective prevention and control measures in this country. Given the global concern around ZIKAV, here, we reviewed current knowledge about global ZIKAV genetic lineages vis à vis the situation in India and discussed future priorities for ZIKAV research in India for effectively designing control strategies.